PENGARUH LEVEL DIVERSIFIKASI, LEVERAGE, RETURN ON ASSET, UMUR PERUSAHAAN, DAN SEKTOR INDUSTRI TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2009 – 2011 - Delinalie Chandra, Yustina Triyani (Jurnal Akuntansi, 2015)
Diversification is the level of business diversity, both in related diversification or unrelated diversification. There are three underlying motive for diversification perspective, namely the market power view, the agency view, and the resource view. In the context of agency theory, agent are tend to apply diversification strategy which can reduce the excess value. Besides that, diversification only can give a complex company system, so that, intern market efficiency will be hard to get. This research used data of manufactures, telecommunication, and transportation, and mining company which listed in Indonesia Stock Exchange during the period of 2009 – 2011. The final samples are 402 item. Multiple regression analysis, statistic descriptive, independent sample t-test, and classic assumption-test. Based on the result, value of the coefficient is less than α (0,005). In variable test, leverage, type of manufacture industries, type of telecommunication, transportation, and hotel industries significant affect excess value. But, return on asset, level of diversification, and firm age not significant influence excess value. Keywords: Excess Value, Diversification, Leverage, Return On Asset, Firm Age